Information Seeking & Documentation as Communication: A Software Engineering Perspective - O'Brien, Michael (Communication & Language at Work, 2014)
Effective communication of knowledge is paramount in every software organisation. Essentially, the role of documentation in a software engineering context is to communicate information and knowledge of the system it describes. Unfortunately, the current perception of documentation is that it is outdated, irrelevant and incomplete. Several studies to date have revealed that documentation is unfortunately often far from ideal. Problems tend to be diverse, ranging from incompleteness, to lack of clarity, to inaccuracy, obsolescence, difficulty of access, and lack of availability in local languages. This paper begins with a discussion of information seeking as an appropriate perspective for studying software maintenance activities. To this end, it examines the importance and centrality of documentation in this process. It finally concludes with a discussion on how software documentation practices can be improved to ensure software engineers communicate more effectively via the wide variety of documents that their projects require.